Heuristics for Dynamic Mapping of Quality Adjustable Applications on NoC-based Reconfigurable Platforms - Nguyen, Van Cuong; Le, Dinh Tuyen; Dao, Vu Tuan; Tran, Thanh Hai; Pham, Ngoc Nam (Old Journal, 2017)
Network on Chip and FPGA-based reconfigurable Systems on Chip are a new trend to provide high performance, flexibility, reducing cost and time to market for the embedded systems. The problem of mapping quality adjustable applications onto heterogeneous NoC-based reconfigurable platforms at run-time with resource constraints while ensuring the maximum overall quality of service of the applications is a big challenge. In this paper, an efficient mapping technique is proposed to solve this problem which consists of a near convex region selection strategy and a dynamic heuristic mapping algorithm. Simulation results show that the proposed technique is very flexible and more than 43% average overall QoS can be achieved compared to some existing solutions. Besides, this technique allows new applications to be easily added to the system in the future.